2014
DOI: 10.1021/mz5001527
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Polymethacrylates Synthesized as Mimics of Tryptophan-Rich Cationic Peptides

Abstract: This study describes a facile and high yielding route to two series of polymethacrylates inspired by the naturally occurring, tryptophan-rich cationic antimicrobial polymers. Appropriate optimization of indole content within each gave rise to polymers with high potency against Staphylococcus epidermidis (e.g., PGI-3 minimum inhibitory concentration (MIC) = 12 μg/ mL) and the methicillin-resistant strain of Staphylococcus aureus (e.g., PGI-3 MIC = 47 μg/mL) with minimal toxicity toward human red blood cells. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 42 publications
1
78
0
Order By: Relevance
“…In addition, guanidine polymers were able to sustain activity in tryptic soy broth (TSB) with fetal bovine serum (FBS) while amine analogs lost their activity. Inspired by the naturally occurring, tryptophan-rich cationic antimicrobial materials, Haeussler and co-workers elegantly designed novel poly(methacrylate) random copolymers [68]. They synthesized methacrylate monomers that mimic the chemical structures of tryptophan, lysine and arginine (Table 1B).…”
Section: Random Copolymersmentioning
confidence: 99%
“…In addition, guanidine polymers were able to sustain activity in tryptic soy broth (TSB) with fetal bovine serum (FBS) while amine analogs lost their activity. Inspired by the naturally occurring, tryptophan-rich cationic antimicrobial materials, Haeussler and co-workers elegantly designed novel poly(methacrylate) random copolymers [68]. They synthesized methacrylate monomers that mimic the chemical structures of tryptophan, lysine and arginine (Table 1B).…”
Section: Random Copolymersmentioning
confidence: 99%
“…The incorporation of AN units in the polycations diminishes the charge density and increases the hydrophobic character of the copolymers, both factors affecting negatively the antimicrobial properties [58,59]. Surprisingly, even acrylonitrile-enriched copolymers (F AN = 0.8) present low MIC values ranging from 16 to 64 lg/mL, considering their low charge density.…”
Section: Antimicrobial and Hemolytic Activitiesmentioning
confidence: 99%
“…2A, C-E) produces a slight and progressive decrease of Table 1 Molar composition of P(AN-co-MTA) copolymers and properties of antimicrobial N-butyl quaternized P(AN-co-MTA-BuI). [35,63,64], introduction of hydrophobic comonomers [59], hydrophobic contra ions [65] etc. Interestingly, the charge density [66] of the copolymers, in terms of mono or biscationic side-chains, does not seem to dramatically affect MIC values.…”
Section: Antimicrobial and Hemolytic Activitiesmentioning
confidence: 99%
“…66 , 67 A tryptophanlike indole monomer, 2-(1H-indol-3-yl)ethyl methacrylate (IEMA), was incorporated into two tryptophan mimicking series -one with a lysine mimic cation source (aminoethyl methacrylate -AEMA; poly(AEMA-IEMA), and the other with an arginine mimic cation source (2-guanidinoethyl methacrylate -GEMA; poly(GEMA-IEMA.) 68 These polymers were evaluated against S. epidermidis and the methicillin-resistant strain of S. aureus for their antimicrobial activity. The tryptophan series exhibited lower antimicrobial activity, compared to hompolymers of GEMA, and were found to be more hemolytic.…”
Section: Fig (23) β-Lactam Monomers Used In Studymentioning
confidence: 99%
“…68 It was found that a carboxylic acid end group significantly reduces haemolysis, which could be attributed to an inter chain complexation. Also, the use of a long alkyl chain on the chain end did increase general membrane activity.…”
Section: Impact Of the Polymer End Groupmentioning
confidence: 99%